Anthropogenic and natural factors shaping the boundaries of the St. Petersburg suburban area - Martynov, Vasily L.; Sazonova, Irina Ye.; Vasilieva, O. Ye.; Grekov, Ivan M.; Sokolova, Natalia V. (Baltic Region, 2024)
The suburban area of St. Petersburg stands out as Russia's most complex in terms of spatial structure, encompassing districts ranging from the suburban imperial residences of the 18th century to low-rise residential zones and modern multi-storey developments of the 21st century. This study concluded that extensive stretches of the administrative border between St. Petersburg and the Leningrad region divide homogeneous territories. Therefore, it makes little academic or practical sense to confine scholarly efforts solely to suburbs situated on one side of this border. The principal factor in delineating the St. Petersburg urban area is the transport accessibility of territories surrounding the city. It was empirically determined that the inner boundary of the suburban area is located approximately within the 40-45-minute isochrone from the city centre, while the outer boundary extends to the 2-hour isochrone. In the conditions of today's St. Petersburg, a two-hour isochrone corresponds to a 60 km distance. Along with isochrones, the actual boundary of the suburban area is determined by several natural and anthropogenic factors. In terms of the natural environment, a significant part of the St. Petersburg suburban area is anthropogenic forest-steppe, whose landscapes are radically different from those of the area’s natural southern taiga subzone. The features of the 'forest steppe' reach their peak to the southwest and south of St. Petersburg. To the north of the city, the suburban zone is defined by both ‘anthropogenic forest-steppe’ and secondary small-leaved forests that have replaced agricultural lands. Another prominent feature is parks found on the premises of former estates where introduced woody species account for a substantial portion of vegetation. The spatial structure of the suburban area north of St. Petersburg is complicated by large extents of unpopulated areas. Since the 19th century, they have divided the area into two virtually disconnected parts.